Use of three-dimensional printing to assess transport vectors in mandibular distraction osteogenesis. Issue 1 (January 2017) - Shah, Sagar; O'Connor, Rory; Watson, Jason; Srinivasan, Dilip; Sidebottom, Andrew
Abstract: It can be difficult to assess the transport vectors for mandibular distraction osteogenesis intraoperatively. Computed tomography (CT) and 3-dimensional digital reconstruction allow "on screen" assessment, but they have limitations, and errors can occur when the 2-dimensional preoperative plan is translated into the operation. We can simulate the operation and reconstruction with 3-dimensional printed models. This allows us to make cutting guides that indicate the position of the osteotomy, which can be extended to position the distractor accurately. The success of this technique relies on close communication with the prosthetic scientist.